Relationship between Facilities, Conditions, Member Participation, and Founding and Maintenance of Dairy Cattle Farmers Group with Entrepreneurship of Its Member in Banyumas Regency - Nuskhi, M; Setiana, Lucie (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2005)
Research was carried out for 12 weeks from May to June 2004 in Kecamatan Ajibarang, Cilongok, Kalibagor, Sokaraja and Purwokerto Timur. Aims of this research were (1) to find out level of entrepreneurship of dairy cattle farmers; (2) to find out relationship between facilities, conditions, member participation, and founding and maintenance of dairy farmers group with entrepreneurship attitude and income rate of its member. A total of 55 respondents (30% of the population) was selected using random sampling. Analysis of rank spearmann was applied to observe relationship between factors. Results showed that (1) entrepreneurship of dairy cattle farmers was on moderate category; (2) members entrepreneurship has not significantly related to factors of facilities, conditions, and member participation, but it has a significant relationship to group founding and maintenance. . (Animal Production 7(2): 111-120 (2005) Key Words: Entrepreneurship, Dairy cattle, Farmers group